Exploring the Influence of Diction and Language Style in Children's Song Lyrics on Preschool Learning and Development - Hartnett, Aron Coffey; Lasslo, Sanner Kenrick; Hertlein, Beach Reynolds (Insan Akademika Publications, 2023)
This research delves into the profound influence of diction and language style within children's song lyrics on the educational experiences of preschoolers. The study investigates the impact of diverse language styles, ranging from simpler, repetitive structures to more complex and varied compositions, on language development, cognitive engagement, emotional responses, and learning outcomes in young children. Through a mixed-methods approach encompassing quantitative analysis and qualitative observations, the research examines the implications of varied language styles on comprehension, engagement, and cognitive growth among preschoolers. Findings highlight the significance of diverse language styles in fostering comprehensive learning experiences, nurturing cognitive engagement, emotional responses, and social interactions among preschoolers. The research underscores the importance of a balanced approach to language styles in educational materials, offering immediate engagement while stimulating cognitive challenge for sustained educational growth. The practical application of these findings advocates for educators to curate a diverse repertoire of song lyrics, integrate multisensory experiences, and harness technology to enhance the learning environment for preschoolers, nurturing their language skills, cognitive abilities, and emotional development. The study's implications extend to educational practices, emphasizing the importance of embracing diverse language styles to create a dynamic and comprehensive educational journey for our youngest learners.